Physics : - Halliday, David (John Wiley & Sons, Inc., 2002)
The 5th edition of "Physics" has been edited to clarify conceptual development in light of recent findings from physics education research, and the mechanics sequence has been re-organized to that energy is a capstone topic. The presentation of thermodynamics and quantum mechanics has been updated to provide a more modern approach, and the end-of-chapter problem sets have been thoroughly over-hauled: new problems added; out-dated reference deleted; and new short-answer conceptual questions added. The supplements package has been expanded to include more materials for student and instructor.